Avulsion fracture of the lesser trochanter in adolescents - Ruffing, Thomas; Rückauer, Tilmann Mathias; Bludau, Frederic; Muhm, Markus Joachim (Injury, 2018)
Avulsion fractures of the lesser trochanter in adolescents are rare. They are a result of a sudden and forceful contraction of the iliopsoas muscle. F…